Decision support in large-scale healthcare information systems: the challenge of integrating ontologies. (14th April 2010) - Price, Colin; Summers, Ron
The growing trend for implementation of healthcare information systems at enterprise and national levels requires the integration of multiple component standards as well as mechanisms for supporting diverse multidisciplinary needs and approaches to care delivery. Most of these large-scale programmes are being undertaken against the context of existing specialist and departmental information systems that often incorporate some decision-support functionality. We explore the issues in defining from these components useful and useable ontologies for decision-support functions in large-scale multidisciplinary healthcare systems.